Assessment of multilayer particleboards produced with green coconut and sugarcane bagasse fibers. (30th April 2019) - Fiorelli, Juliano; Bueno, Stephen Bonilla; Cabral, Matheus Roberto
Highlights: Multilayer particleboards based on waste fibers were assessed. Physical, mechanical, thermal and accelerated aging properties were evaluated. Assessed physical properties meet the standard requirements for wood-based materials. Assessed mechanical properties meet the minimum values for wood-based materials. Abstract: The use of alternative raw materials to produce particleboards become an interesting strategy to replace wood and dampen the deforestation that have created environmental issues. Thus, this paper aims to assess the physical, mechanical, thermal and aging properties of multilayer particleboards produced with green coconut and sugarcane bagasse fibers. The particleboards were produced with two different densities (500 and 700 kg/m 3 ) consisting of 3 layers: two outer layers (OL) of sugarcane bagasse fiber and one inner layer (IL) of green coconut fiber bonded with castor oil polyurethane resin (PU-resin). The physical, mechanical, thermal and accelerated aging properties of the particleboards were measured by advance equipment. The X-ray densitometry identified variations in the density profile across the thickness of the particleboards. Regarding the assessed mechanical properties, the particleboards produced with a density of 500 kg/m 3 (T1) meet all the ANSI A208.1-1999 requirements for LD-1 particleboards. On the other hand, the particleboards produced with a density of 700 kg/m 3 (T2) only meet ANSI A208.1-1999 requirements for M-2 particleboards. The results of the fatigue tests indicated that all the particleboards assessed were able to survive a fatigue life of 40.000 cycles at stress levels equal to 25% of the breaking load. Accelerated aging assessment shown that this test caused degradation of the particleboards and indicated that the exposure conditions (temperature, humidity, UVA and UVB) caused permanent damage to the physical properties of WA and TS as well as the mechanical properties.